Electrochemical Corrosion Testing 1981
DOI: 10.1520/stp28024s
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Reference Electrode Techniques in Localized Corrosion

Abstract: The principles, advantages, and implementations of scanning reference electrode techniques are reviewed. The technique locates the position of localized corrosion, and can be used to monitor the development of corrosion and changes in the corrosion rate under a wide range of conditions. Data related to pitting, intergranular corrosion, welds, and stress-corrosion cracking are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 30 publications
2
66
0
Order By: Relevance
“…Measurements of the physical separation of anodic and cathodic areas, the currents flowing between them as well as the mapping of potentials in electrolytic solutions have been successfully used for the study of the processes of localised corrosion of different systems (Isaacs & Vyas, 1981;Tuck, 1983;Bates et al, 1989;Sargeant et al, 1989;Trethewey et al, 1994;Trethewey et al, 1996;McMurra et al, 1996;McMurray & Worsley, 1996). A schematic drawing of a local corrosion cell is shown in figure 10.…”
Section: Studies Of Localised Corrosion Using the Scanning Reference mentioning
confidence: 99%
“…Measurements of the physical separation of anodic and cathodic areas, the currents flowing between them as well as the mapping of potentials in electrolytic solutions have been successfully used for the study of the processes of localised corrosion of different systems (Isaacs & Vyas, 1981;Tuck, 1983;Bates et al, 1989;Sargeant et al, 1989;Trethewey et al, 1994;Trethewey et al, 1996;McMurra et al, 1996;McMurray & Worsley, 1996). A schematic drawing of a local corrosion cell is shown in figure 10.…”
Section: Studies Of Localised Corrosion Using the Scanning Reference mentioning
confidence: 99%
“…Nevertheless, the ability to locate and monitor active pits led to interesting measurements regarding the pitting. Details of other localized corrosion processes were also investigated by Vyas (8,9). Figure 3 shows a scanning reference electrode measurement over an electropolished 304 stainless steel during immersion in FeCl 3 solution.…”
Section: Pitting Corrosionmentioning
confidence: 99%
“…It allows the precise identification of probe position above the surface of specimen [12]. It has been shown that this technique is powerful in many different applications, such as using a calibration technique by which localized current densities can be measured by mapping corrosion surface damage [13,14].…”
Section: Introductionmentioning
confidence: 99%